The immunomodulatory effects of Regenerative Mesenchymal Stem Cells in Neurodegenerative diseases - Alrehaili, Amani (Jour Med Resh and Health Sci, 2023)
Neurodegenerative disease is a chronic, life-threatening central nervous system disorder marked by neuronal damage or apoptotic death. With current therapies, the disease cannot be cured. Regeneration medicine is a branch of medicine that makes use of the ability of stem cells to regenerate damaged tissues and organs. Therefore, regenerative medicine refers to all procedures that involve stem cells that have been properly identified and harvested before being locally stimulated to multiply and differentiate in order to be transplanted in the interest of regeneration. Cell therapy, particularly the application of mesenchymal stem cells (MSCs), is one feasible alternate approach. MSCs are pluripotent stem cells that can self-renew and differentiate in multiple pathways. MSCs may offer a reliable source of nerve cells for cell therapy or transplantation. With an emphasis on Parkinson's disease, Alzheimer's disease, and Amyotrophic Lateral Sclerosis, the current review assessed the evidence for MSC treatments in neurodegenerative illnesses. In addition, it analyzed possible MSC modes of operation and outlined a few problems with MSC-based stem cell therapy. Overall, the current review presented MSCs therapeutic processes and how they might improve treatments for neurodegenerative diseases.